Survey on some key technologies and development trends of luxury cruise ship - Jiapeng SUN (Zhongguo Jianchuan Yanjiu, 2022)
The design and construction of luxury cruise ships is currently a hot topic in the domestic shipbuilding industry, but the design skills are insufficient due to a lack of practical experience derived from real projects. First, based on a survey of the internal R&D and refitting design of luxury cruise ships and ferry/passenger ship projects with gross tonnages of 15 000–75 000, as well as referring to the latest developments in rules regarding cruise and passenger ships, and the design features of delivered ships across the world, this paper seeks to review the relevant advanced technologies employed in the international design and construction of luxury cruise ships, with a focus on 3D modelling, flexible design throughout the full life cycle, holistic ship performance optimal design and alternative design application. Moreover, the effects of the application of green fuel, digital and intelligent design, and health and hygiene safety requirements on the future design of cruise ships are discussed. It is hoped that this paper can provide valuable references for improving the domestic design level of luxury cruise ships.